Cytolytically active murine T-cell hybrids. - Nabholz, M; Cianfriglia, M; Acuto, O; Conzelmann, A; Haas, W; von Boehmer, H; McDonald, H; Pohlit, H; Johnson, J (1980)
Following the demonstration that hybrids between normal B-lymphocytes and myeloma cell lines continue to secrete antibodies with the same specificity as those produced by the parental B-cells, many groups have tried to use this approach to obtain cell lines expressing T-lymphocyte functions by crossing thymoma lines not expressing any measurable activity with various types of T-cell populations. Although there have been reports that hybrids could be isolated which secrete T-cell products with immunological activity, efforts to produce functionally active hybrids from cytolytic T-cells have all been unsuccessful (refs 6, 7, and M. N. and H. D. Engers, unpublished). We have fused an established, T-cell growth factor (TCGF)-dependent murine cytolytic T-lymphocyte (CTL) line with a mouse thymoma line and have obtained hybrids with cytolytic activity when we selected the hybrids in TCGF-containing medium, while hybrids isolated in the absence of growth factor showed no detectable cytolytic potential.